Describing Translation Techniques Used in the Translation of Culturally Bound Terms in West Java Calendar of Event 2020 - Dyah Raina Purwaningsih; Nadia Gitya Yulianita (The English Department, Faculty of Humanities & Creative Industries, Petra Christian University, 2024)
This research aims at analyzing translation techniques used by the translator in translating the booklet